States of water in proton exchange membranes: Part A - Influence of chemical structure and composition. (24th February 2017) - Roy, Abhishek; Hickner, Michael A.; Lee, Hae-Seung; Glass, Tom; Paul, Mou; Badami, Anand; Riffle, Judy S.; McGrath, James E.
Abstract: Disulfonated poly(arylene ether) and polyimide copolymers can phase separate to form nanoscale hydrophilic and hydrophobic domain morphology. Water in these domains has been assigned to three different states, tightly bound, loosely bound and free water. The states of water were characterized using DSC, NMR relaxation and TGA. The chemical structures of the proton exchange membranes were varied in chemical composition, microstructure (random and block) and also regarding functional sulfonic acid groups fixed to the polymer backbones. A strong dependence of the types of water on the ion content and morphology was observed. For the random copolymers, the formation of free water in the system occurs after reaching a certain ion content. For the multi-blocks, in addition to the ion content, free water also develops with increasing block lengths. The formation of continuous morphology in the copolymers was correlated to the onset of free water. Influences of the states of water on PEM transport properties will be reported separately. Graphical abstract: Highlights: States of Water in Proton Exchange Membranes: Part A – Influence of Chemical Structure and Composition. This article characterizes and quantifies three different states of water absorbed in disulfonated aromatic polyelectrolytes. A critical threshold of free water is correlated with a morphological change.